2023
DOI: 10.1186/s12887-023-04236-2
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural factors associated with detection of autism among culturally and linguistically diverse communities in Australia

Aniqa Hussain,
James Rufus John,
Cheryl Dissanayake
et al.

Abstract: Background The age at which parents or caregivers first develop concerns about their child’s development has significant implications on formal diagnosis and intervention. This study aims to determine the sociocultural factors that are associated with the age and type of first concern reported by parents of autistic children among culturally and linguistically diverse (CALD) communities in Australia. We also assessed whether sociocultural factors predict autism traits measured in terms of socia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…It has been noticed that, the majority of our ASD cases diagnosis was after 2 and 3 years of age. Which was reliable with that seen in Australia, where a study conducted on a larger sample of autistic cases, the average age of diagnosis was 28 months [13] . Another study done recently in 2022, in which 61% of children with autism were diagnosed between (3-6) years of age [9] .…”
Section: Discussionsupporting
confidence: 87%
“…It has been noticed that, the majority of our ASD cases diagnosis was after 2 and 3 years of age. Which was reliable with that seen in Australia, where a study conducted on a larger sample of autistic cases, the average age of diagnosis was 28 months [13] . Another study done recently in 2022, in which 61% of children with autism were diagnosed between (3-6) years of age [9] .…”
Section: Discussionsupporting
confidence: 87%
“…The possible cause due to psychological factors of parents during pregnancy, psychological factors of children, the role of parents in the development phase of children's speech period, and the role of teachers and the environment in schools that help children in enriching vocabulary. Another reason for speech/language delay of children could be due to cultural beliefs of parents where speech delays are often normalised or overlooked (Hussain et al, 2023b).…”
Section: Discussionmentioning
confidence: 99%
“…Ou et al (14) found that even if the mother spoke English pro ciently, infants from culturally and linguistically diverse (CALD) communities were less likely to access health services and receive mental health interventions. A study by Hussain et al (15) found a signi cant link between CALD status and delayed age at which developmental concerns were raised, as well as higher severity of autism symptoms at the time of professional input. In this regard, a multicultural cohort study found an inverse care law in that those from the most disadvantaged backgrounds with the highest risk for developmental problems were least likely to engage with developmental Page 3/20 surveillance programs for early identi cation, thereby missing opportunities for early intervention (13,16).…”
Section: Introductionmentioning
confidence: 99%